2019
DOI: 10.31234/osf.io/pue6f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-method confirmatory factor analyses of puberty in early adolescent girls

Abstract: (full):Correctly measuring and operationalizing pubertal processes during development is important for capturing variation in both normative development and trajectories associated with adverse outcomes. The aim of the current study was to understand how this variance may be captured by different pubertal processes (adrenarche and gonadarche) and how multiple methods may contribute to variance (and how they are correlated). The study explored multi-method cross-sectional pubertal data, including self-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…The pubertal latent factor found here, which included 5 out of the 6 explored markers of sexual maturation chosen because they are considered not to be entirely redundant (Van Hulle et al, 2015;Worthman et al, 2019; see also Byrne et al, 2019), confirmed findings from Shirtcliff et al (2009) regarding the associations of Tanner ratings, PDS scores and DHEA, but not the significant relations of most of these variables with testosterone. Shirtcliff et al (2009), however, separated PDS scores into gonadal and adrenal indicators, so their results cannot be directly contrasted with ours.…”
Section: Adequacy Of the Metabolic And Pubertal Status Latent Factorsupporting
confidence: 73%
See 1 more Smart Citation
“…The pubertal latent factor found here, which included 5 out of the 6 explored markers of sexual maturation chosen because they are considered not to be entirely redundant (Van Hulle et al, 2015;Worthman et al, 2019; see also Byrne et al, 2019), confirmed findings from Shirtcliff et al (2009) regarding the associations of Tanner ratings, PDS scores and DHEA, but not the significant relations of most of these variables with testosterone. Shirtcliff et al (2009), however, separated PDS scores into gonadal and adrenal indicators, so their results cannot be directly contrasted with ours.…”
Section: Adequacy Of the Metabolic And Pubertal Status Latent Factorsupporting
confidence: 73%
“…To the best of our knowledge, a latent factor using various subjective and objective pubertal indicators has only been built once, in a recent non-peer reviewed preprint (Byrne et al, 2019) that sampled 10-to 13-year-old girls and used different pubertal indicators, which is not directly comparable to our own work. Still, the theory driven inclusion of variables in the model and its internal consistency (i.e.…”
Section: Adequacy Of the Metabolic And Pubertal Status Latent Factormentioning
confidence: 99%
“…Relatedly, another potential limitation of the present study was the measure of pubertal development. Recent evidence indicates that self-report (e.g., PDS) and hormonal measures both meaningfully contribute to assessment of pubertal development (Byrne et al, 2019), and so future work will benefit from employing multiple sensitive self-report and physiological measures of pubertal development (Ladouceur et al, 2019). It is also notable that many of the daughters reported being in relatively advanced puberty, suggesting that puberty may not be an ideal measure of developmental progress in a sample aged 10 to 19; however, supplemental analyses conducted with age instead of pubertal development (see Tables A and B in the online supplemental material) obtained comparable results to those derived using the PDS, thereby providing further support for the findings presented here.…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of these inter-individual changes in terms of age of onset and end of puberty, which do not follow a linear trajectory, has contributed to the growing interest in exploring pubertal effects on cognition and behavior in the last few decades (Marceau et al, 2019). During this period, many recommendations have been proposed regarding ways to incorporate pubertal measures in developmental studies (Byrne et al, 2019;Cheng et al, 2021;Dorn, 2006Dorn, , 2015Dorn and Biro, 2011;Dorn et al, 2006;Huang et al, 2009;Mendle et al, 2019). However, conceptual difficulties remain.…”
Section: Puberty and Cognitive Development During Adolescencementioning
confidence: 99%
“…Latent pubertal measures could even be improved over time by adding more measures as new methods and biomarkers are developed. The incorporation of latent constructs in studies involving puberty has been called for before (Dorn and Biro, 2011) and we have seen recent steps in this direction (Byrne et al, 2019;Herting et al, 2021), although there is still a long way to go before this strategy becomes widespread. We discuss this issue further in França et al (2022).…”
Section: Issues With Pubertal Measuresmentioning
confidence: 99%